Morpho-Molecular Charactrization of Endophytic Fungi Associated With Aquilaria Malaccensis Lam. - Zafrin, Mehnaz; Shamsi, Shamim; Noman, Md Abdullah Al (Bangladesh Journal of Plant Taxonomy, 2024)
A total of 26 fungal isolates were identified from Aquilaria malaccensis Lam. (Agarwood). Among them Aspergillus flavus Link type-1, Aspergillus flavus Link type-2, Aspergillus niger Tiegh. type. 1, Aspergillus niger Tiegh. type. 2, Aspergillus sp. 1, Aspergillus sp. 2, Alternaria alternata (Fr.) keissl., Curvularia lunata (Wakker) Boedijn, Penicillum digitatum (Pers.) Sacc., Penicillium commune Thom, Penicillum italicum Wehmer, Penicillium sp. 1, Penicillium sp. 2, Penicillium sp. 3, Penicillium sp. 4, Eupenicillium sp. 1, Eupenicillium sp. 2, Sphaeropsis sp. Sacc. and Harknessia sp. Cooke. were identified by morphological analysis and Alternaria tenuissima (Kunze) Wiltshire, Alternaria palandui Ayyangar, Fusarium sporotrichioides Sherb., Lasiodiplodia theobromae (Pat.) Griffon & Maubl., Lasiodiplodia pseudotheobromae A.J.L. Phillips, A. Alves & Cronus, Diaporthe hongkongensis R.R. Gomes, Glienke & Cronus and Diaporthe perseae (Zerova) R.R. Gomes, Glienke & Cronus were identifed upto genus level by morphological analysis, which were later on identified and confirmed at species level by molecular analysis. Among these isolated fungal species- Alternaria palandui, Diaporthe hongkongensis, Diaporthe perseae and Lasiodiplodia pseudotheobromae have been reported as newly recorded species and Harknessia sp. and Sphaeropsis sp. were reported as new generic records for Bangladesh. Bangladesh J. Plant Taxon. 31(1): 141-154, 2024 (June)